Studying yield components and attractions indices in common bean (Phaseolus vulgaris L.) accessions in the Northern Zone of the Volga-Akhtuba Floodplain - A. P. Ivakin; A. A. Grushin (Труды по прикладной ботанике, генетике и селекции)
Background. Despite the value of common beans as a food product, the area under this crop in Russia is quite small and the assortment of commercialized cultivars is limited. In this regard, a vital breeding trend for common bean in this country is still the development of new cultivars, more high-yielding and adapted to various areas of cultivation. To solve this problem, an advanced science-based search for breeding sources is required. Materials and methods. The research was carried out at Volgograd Experiment Station of VIR by conventional methods. Fifty-nine common bean accessions from the collection of VIR were altogether studied to determine their precocity, yield components and attraction indices. Statistical data processing and correlation analysis of the results were carried out. Results and conclusions. A comparative study of common bean accessions belonging to different earliness groups was conducted. Differences in the degree of variability were identified for yield components and macro- and micro-attraction indices. For a majority of traits, early-ripening accessions exceeded medium and late ones in the degree of variability. Strong positive correlations were observed between the seed weight per one plant and such characters as the number of pods, aggregate weight, weight of pods, and weight of valves. The index of micro-attraction practically did not correlate with productivity in early accessions, and only slightly correlated in medium/late ones, so it seems inexpedient to use the micro-attraction index in common bean breeding for higher yield in the region. Accessions with high maximum yield rates were selected mainly from the group of early-ripening accessions, and those with high macro-attraction levels, from the group of medium/late ones. In view of their obvious advantages, it is early cultivars that should be recommended for yield-targeted common bean breeding in the northern areas of the Volga-Akhtuba Floodplain. Special attention needs to be paid to the accessions ‘Code 128’ (k-15261), ‘Bertires’ (k-15262) and ‘Oxy Amidor’ (k-15269). The medium- or late-ripening accessions ‘Jetta’ (k-14689), ‘Prima’ (k-14687) and ‘Zlute’ (k-15127) are recommended to be used in breeding for micro-attraction